Synthesis of colloidal MoSx nanoparticles and their transformation into carbon supported MoS2nanocomposite - Ghosh S.; Azad U.P.; Singh A.K. (My University, 2025)
Carbon supported MoS2 nanocomposite has been extensively used as a catalyst for hydrogen evolution reaction as well as hydrotreating process. However, their synthesis method majorly involves post-synthetic installation of MoS2 nanoparticles or sheets on the carbon support via hydrothermal reaction or high-temperature sulfidation of molybdenum oxide precursors. Herein, highly dispersed low-dimensional MoSx nanoparticles (NPs) with a particle size as small as 2.4±0.6 nm were successfully synthesized by purging H2S into the polyoxomolybdate solution (A3[PMo12O40]; A+ = H+, NH4+) in the presence of different capping agents (SDS and PVP). Furthermore, these MoSx nanoparticles was found to exhibit excitation-wavelength-dependent photoluminescence behavior.Upon annealing of capping agent stabilized MoSx nanoparticles at 450 °C for 6 h in Ar atmosphere, in-situ carbonization of capping agents (SDS/PVP) has occurred which led to the formation of amorphous carbon supported MoS2 nanocomposite. The formation of amorphous carbon was verified using FT-Raman spectroscopy study whereas the presence of MoS2 was established with the help of XRD, TEM, SAED, XPS, and FT-Raman spectroscopy techniques. The small size of the precursor MoSx nanoparticles was presumed to be the driving force for the formation of highly disperse few layers of MoS2 wherein surface ligands dehydrogenated and polymerized to form the amorphous carbon supports for the as-formed few layers of MoS2, hence control their final size of the particles.Synthetic ease of the as prepared carbon supported MoS2 nanocomposite may encourage the effective application of this materials for heterogeneous catalysis and electrochemical applications. © 2019 American Institute of Physics Inc.. All rights reserved.